2019
DOI: 10.1021/acs.nanolett.9b03556
|View full text |Cite
|
Sign up to set email alerts
|

Reactive Oxygen Correlated Chemiluminescent Imaging of a Semiconducting Polymer Nanoplatform for Monitoring Chemodynamic Therapy

Abstract: In chemodynamic therapy (CDT), real-time monitoring of reactive oxygen species (ROS) production is critical to reducing the nonspecific damage during CDT and feasibly evaluating the therapeutic response. However, CDT agents that can emit ROS-related signals are rare. Herein, we synthesize a semiconducting polymer nanoplatform (SPN) that can not only produce highly toxic ROS to kill cancer cells but also emit ROS-correlated chemiluminescent signals. Notably, the efficacy of both chemiluminescence and CDT can be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
99
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 131 publications
(107 citation statements)
references
References 52 publications
1
99
0
Order By: Relevance
“…In the absence of luminol, no CL signal can be collected from Co SACs-H 2 O 2 mixture. The results reveal that the CL signalo riginated from typical luminol reaction insteado f 1 O 2 .A ccording to our experimental results and some previous literatures, [7] a possible mechanism of luminol-H 2 O 2 CL reactionb oosted by Co SACs is elucidated in Equations (1)- (5).…”
supporting
confidence: 78%
See 1 more Smart Citation
“…In the absence of luminol, no CL signal can be collected from Co SACs-H 2 O 2 mixture. The results reveal that the CL signalo riginated from typical luminol reaction insteado f 1 O 2 .A ccording to our experimental results and some previous literatures, [7] a possible mechanism of luminol-H 2 O 2 CL reactionb oosted by Co SACs is elucidated in Equations (1)- (5).…”
supporting
confidence: 78%
“…However,t he naturale nzyme-based catalysts for CL reaction are always limited by high cost, easy denaturationa nd low stability. [4] Some small-molecular catalysts such as metalc omplexes and porphyrins [5] also display catalytic activity for some CL reactions. Despite their ideal chemical stability and low cost, the insufficient catalytic efficiency cannoty et meet the demand of highly intensivee mission.…”
mentioning
confidence: 99%
“…It has acquired the consensus view that endogenous H 2 O 2 can be decomposed into • OH with the assistance of extraneous Fe 2+ ions to ensure satisfactory therapeutic outcomes (Chen, Huang, et al, 2020; Zhao et al, 2019). Therefore, Fe‐based chemical‐driven ROS‐ECBs are promising application potential for CDT, including Fe 3+ ions‐based coordination polymers (Lei, Zhang, Zheng, Liu, & Xie, 2018; Wang et al, 2020), Fe‐based amorphous metals and alloys (Yang et al, 2019), and Fe 3 O 4 and their derivatives (Ma et al, 2019; Zhang et al, 2018). For instance, Huo et al (2017) constructed TME‐responsive GOD‐Fe 3 O 4 @DMSNs for efficient cancer therapy (Figure 4b).…”
Section: Energy‐converting Biomaterials For Cancer Therapymentioning
confidence: 99%
“…PTT is an emerging cancer‐treatment modality that mainly relies on high‐performance photo‐converted H‐ECBs. To date, numerous inorganic biomaterials, such as noble metal‐, metal–semiconductor‐, and two‐dimensional‐biomaterials, and organic materials including small molecules and semiconducting polymers have been explored as the potential candidates for PTT (Wang, Shi, et al, 2020). Compared with the organic biomaterials, inorganic counterparts possess high photothermal‐conversion efficiency (PCE) and photo‐stability but suffer from poor biodegradability (Li et al, 2017).…”
Section: Energy‐converting Biomaterials For Cancer Therapymentioning
confidence: 99%
“…[33] Its LUMO and HOMO energies are −0.93 and 1.61 eV (vs NHE), [34] while the CB and VB energies of Bi 2 Se 3 are −0.25 and 0.89 eV (vs NHE), [25] which means hemin and Bi 2 Se 3 could form heterostructure according to the heterostructure theory. [9] More importantly, it has been reported that hemin not only showed Fenton catalytic activity, [35][36][37] but also acted as mimetic peroxidase for H 2 O 2 detection application, since Fe(III) existed at the center of protoporphyrin IX. [38] Thus, hemin has the potential to meet the aforementioned requirements.…”
Section: Introductionmentioning
confidence: 99%